Neutrophils, not macrophages, aid phage-mediated control of pulmonary Pseudomonas aeruginosa infection - Weissfuss, Chantal; Hoffmann, Karen; Behrendt, Ulrike; Bürkle, Magdalena; Twamley, Shailey G.; Korf, Imke H. E.; Ahrens, Katharina; Rohde, Christine; Zobel, Christian M.; Debarbieux, Laurent; Ricard, Jean-Damien; Witzenrath, Martin; et al. (Frontiers in Immunology, 2025)
BackgroundThe increasing prevalence of multidrug-resistant (MDR) bacteria has reduced the effectiveness of standard antibiotics, prompting renewed interest in bacteriophage (phage) therapy as an alternative or adjunctive treatment. Phage therapy offers high specificity, self-amplification at infection sites, and minimal disruption to the gut microbiota. However, clinical implementation is challenging, due to the risk of phage resistance and uncertainties regarding optimal dosing and immune interactions.MethodsPreviously, we demonstrated that a two-phage cocktail exhibited low immunogenicity in mice and, when combined with meropenem, significantly improved clearance of ventilator-associated Pseudomonas aeruginosa pneumonia, reduced inflammation, and disrupted biofilms more effectively than either treatment alone. In the present study, we investigated the interplay between this phage cocktail and innate immune defenses using a murine respiratory infection model and human in vitro assays.ResultsOur findings reveal that the therapeutic efficacy of phage treatment is critically dependent on the presence of neutrophils, which act synergistically with phages to achieve effective bacterial clearance, particularly when bacterial burden exceeds a defined threshold. Alveolar macrophages, however, do not significantly contribute to infection resolution in vivo.ConclusionSince neutrophils play a key-role in supporting phage-mediated Pseudomonas clearance, the efficacy of phage therapy is closely linked to the hosts immune competence – an important consideration when treating immunocompromised patients.